Simplify the given expression. –10xy(4xy3 – 7xy + 9y2)
–40x2y4 – 7x2y2 + 9x2y3

–40x2y4 + 70xy + 90y2

–40x2y4 + 70x2y2 – 90xy3

–40x2y4 – 7xy + 9y2

Respuesta :

gmany

Answer:

[tex]\large\boxed{-40x^2y^4+70x^2y^2-90xy^3}[/tex]

Step-by-step explanation:

Use the distributive property a(b + c) = ab + ac:

[tex]-10xy(4xy^3-7xy+9y^2)\\\\=(-10xy)(4xy^3)+(-10xy)(-7xy)+(-10xy)(9y^2)\\\\\text{use}\ a^na^m=a^{n+m}\\\\=-40x^{1+1}y^{1+3}+70x^{1+1}y^{1+1}-90xy^{1+2}\\\\=-40x^2y^4+70x^2y^2-90xy^3[/tex]

Otras preguntas